Contrasting niche dynamics in the invasion processes of two congeneric dinoflagellates - Rafael Lacerda Macêdo (Scientific Reports)
Abstract Niche-based models are essential for predicting invasion risks. Although most invasive species tend to conserve their ecological niches after introduction, some challenge this assumption by expanding or contracting their niches, yet such patterns remain underexplored in microorganisms. Since larger niche shifts can reduce the predictive performance of these models, this study examines whether the climatic niches of the invasive dinoflagellates Ceratium hirundinella (Müller, 1841) and C. furcoides (Langhans, 1925) have shifted following their invasion from native European to non-native American ranges, where they have caused significant impacts on biodiversity and water quality. Though both species are native to temperate European lakes, their colonization patterns in the Americas differ, and the drivers of their spread remain unclear. In this study, niche conservatism was analyzed using five niche dynamic metrics for both species. The current distribution of C. hirundinella primarily in subtropical and temperate non-native areas aligns with its native climate (i.e., higher niche stability), suggesting preadaptation. Meanwhile, for C. furcoides, a niche shift—indicated by maximum expansion and unfilling—suggests a much higher potential for rapid spread across both tropical and subtropical climates. These findings show distinct climatic responses of congeneric species in non-native ranges, emphasizing the need to move beyond native environmental predictors when assessing invasion risk. Future research should explore niche shifts over time and whether invasions begin in ecologically matched habitats (as expected for C. hirundinella) or are driven by propagule pressure and human activity despite niche mismatches (as in C. furcoides).